Transduction, systems, networks: a theoretical-methodological complementary triad in the study of technosocial reality - Sayapin, Vladislav Olegovich (Философия и культура, 2025)
The article offers an innovative theoretical and methodological framework for analyzing technosocial reality through the synergy of three approaches: transduction (G. Simondon), systems theory (N. Luhmann), and network analysis (M. Castells). In conditions of digital turbulence, when traditional disciplinary models fail to explain the dynamics of hybrid systems (algorithms, digital platforms, cyber-physical spaces), this triad overcomes the limitations of reductionism. Transduction reveals the mechanisms of spontaneous genesis of novelty, network theory maps out the flows of resources and power, while the systemic approach provides the tools for understanding the resilience of structures in a metastable environment. The complementarity of these perspectives allows for capturing the key dynamics of the formation of modernity, which includes significant factors: processuality, nonlinearity, and conflict, inaccessible to each paradigm separately. This theoretical "alchemy" transforms the methodological crisis of the digital age into a powerful tool, where the metastability of technosocial formations acquires intelligible contours. The methodological toolkit of the article is based on the sequential application of four complementary methods within the framework of the complementary triad (Simondon – Luhmann – Castells): comparative analysis, case-oriented modeling, genetic-structural method, and dialectical hermeneutics. This synthetic framework overcomes the static nature of traditional methods, replacing linear causality with the analysis of feedback loops in procedural reality. The key task of the methodology is to unveil the complementary triad for subsequent effective understanding of the contingent and recursive process of the technosocial phase of individuation, producing operationally closed (autoethetic) systems. The study synthesizes three heterogeneous theoretical traditions for the first time, creating a language for analyzing the elusive ontology of the digital age, where human and non-human actors co-evolve through autopoiesis, transductive leaps, and network topologies. The relevance of the work is determined by the crisis of classical sociocultural methods in the face of phenomena such as artificial intelligence in management, which not only executes commands but generates solutions based on data, or blockchain communities that are decentralized around distributed ledger technologies. The practical significance of the approach lies in the development of tools for: forecasting points of bifurcation in technosocial systems (at the intersection of Simondonian metastability and Luhmannian selection); deconstructing the power of algorithms through the lens of network asymmetry (Castells) and operational closure (Luhmann); and the ethical design of digital environments where transduction becomes the creation of a new metastable state of the system.